Anaerobic digestion of swine manure using aqueous pyrolysis liquid as an additive. (March 2020) - Yu, Xiunan; Zhang, Congguang; Qiu, Ling; Yao, Yiqing; Sun, Guotao; Guo, Xiaohui
Abstract: As a very typical agricultural organic waste, the anaerobic treatment of swine manure requires more mechanistic exploration to improve the efficiency and quality of its conversion to renewable energy. The feasibility of using aqueous pyrolysis liquid (APL) as anaerobic digestion (AD) substrate has been verified, however only few applications of APL as an additive to AD have been reported. The application of diluted APLs (5 times dilution (A5), 50 times dilution (A50), and 100 times dilution (A100)) as an additive in AD of swine manure was investigated. The result showed that the effects of different concentrations of APL on AD are different. A50 improved methanogenic capacity by 22.98 ± 5.82% compared to control because of trace elements in APL, which both enhanced resistance of microorganisms to high ammonia nitrogen (TAN) concentration, and reduced TAN accumulation. Accordingly, the average dissolved organic carbon (DOC) concentration for A50 was lower than in the control. Based on microbial communities, the dominant volatile fatty acids (VFAs) were degraded mainly by Methanosarcina and Methanobrevibacter . The versatile metabolic pathways and high relative abundance of Methanosarcina for A50 rationalized the high methane production. Therefore, the use of APL as an additive has considerable potential of application. Graphical abstract: Image 1 Highlights: Aqueous pyrolysis liquid (APL) as an additive in anaerobic digestion (AD) was studied. Concentration of APL had effects on methane yield from swine manure. Low concentration of APL promoted methane yield from swine manure by 23.0%. Phenol contained in 50 times diluted APL stimulated the genus Methanosarcina growth. Variation of methane production was dose-dependent.